Investigations of Cutting Tool Wear While Machining Inconel 718 - Petru, Jana; Schiffner, Jan; Zlamal, Tomas; Sadilek, Marek; Stancekova, Dana (Manufacturing Technology Journal, 2015)
This contribution describes the progress of wear and influences contributing to wear of a cutting tool during straightturning of the Nickel superalloy Inconel 718 according to W. Nr 2.4668. According to the ISO 513 standard this alloy belongs among heat resistant materials; it is a special Nickel alloy used primarily for machine parts in the aircraft industry. The experimental part was done for the purpose of testing suitability of proposed exchangeable cutting inserts intended for machining of Inconel 718. Mechanisms and magnitude of wear and durability of the tools were determined in accordance with the ISO 3685:1993 standard in order to evaluate suitability of the proposed tools.
Keywords: Inconel 718; machining; cutting tool; durability; mechanism and criteria of wear